Pengaruh Mekanisme Corporate Governance, Kinerja Keuangan dan Kinerja Lingkungan terhadap Pengungkapan Islamic Social Reporting - Mahardhika Kurniawati; Rizal Yaya (Journal of Accounting and Investment, 2017)
The objective of this research is obtain empirical evidence about the effect of commissioner board size, commisioner board independence, audit committee size, profitability, and the environmental performance on Islamic Social Reporting (ISR) of companies which are in the Sharia Securities List (DES). The population of this research consisted of all companies under DES which joined PROPER environmental rating during 2011-2015. There were 31 companies were selected as samples based on purposive sampling method. The method employed to measure the ISR Disclosure was content analysis by scoring the items of social disclosure in the annual report of those companies. The multiple linier regression shows that the size of commisioner board, profitability, and environmental performance have positive effects on the disclosure of Islamic Social Reporting, while the independence of commisioner board and audit committe do not affect the disclosure of Islamic Social Reporting.